Digital media technologies and the contributions they make to the sustainability of community radio stations – The example of Izwi LoMzansi FM - Dube, Sakhile (University of the Witwatersrand, Johannesburg, 2024)
This study investigates the impact of digital media technologies, specifically mobile applications, and social media, on the sustainability of community radio stations. It places particular emphasis on three facets of sustainability: social, institutional, and financial, using Izwi LoMzansi FM as the case of the study. Community radio stations encounter significant sustainability hurdles, such as suboptimal programming and financial constraints, which hinder their ability to fulfil their democratic roles. While digital media technologies are revolutionising the community broadcasting scene in South Africa, local radio stations have been slow to adjust. This highlights the pressing need for these stations to attain economic self-reliance to maintain autonomy and interact effectively with advertising sectors. The research findings reveal that digital media technologies have the potential to contribute to the sustainability of Izwi LoMzansi FM, albeit with modest impacts in terms of social and institutional sustainability, and relatively limited effects on financial sustainability. Despite progress in leveraging digital media tools to enhance sustainability, the station faces persistent challenges, including high personnel turnover, a lack of specialised expertise in digital media technologies, the necessity for dedicated leadership to drive digital revenue, and the imperative to address the digital divide in terms of access and usage.
A research report submitted in fulfillment of the requirements for the Master of Arts in Journalism and Media Studies, In the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Digital media technologies; community radio stations; social media; sustainability; mobile application; SDG-9: Industry, innovation and infrastructure